Oral Health Care Management in Atypical Oral and Cutaneous Bullous Pemphigoid - Widowati, Kharinna; Dewanthy P, Sri; Lukisari, Cane; Nafi’ah; Setianingtyas, Dwi; Rahman, Kurnia Hayati; Libriansyah; Riyanto, Eko; Damaiyanti, Dian W; Ayuningtyas, Nurina F. (Denta Journal Kedokteran Gigi, 2026)
Background: Bullous Pemphigoid (BP) is the most common subepidermal bullous autoimmune disease, typically presenting as tense bullae. Atypical presentations of bullous pemphigoid often mimic TEN or impetigo, creating diagnostic ambiguity. Effective management of these cases requires integrated strategies to address systemic health factors and extensive oral mucosal involvement. Objective: This report highlights the Oral Health Care Management of atypical oral and cutaneous manifestations of Bullous Pemphigoid. Case: A 58-year-old woman with a history of Diabetes Mellitus and heart disease was referred with extensive bullae, erosions, and "honey-like" crusts involving over 30% of her body surface area. Her condition worsened despite two weeks of treatment with acyclovir, which was administered for suspected herpes. The presentation was highly suggestive of TEN and impetigo. Case Management: Management of the oral and perioral lesions focused on infection prevention and pain relief. Debridement was performed using sterile gauze soaked in normal saline and 0.2% chlorhexidine. This was followed by the application of Aloevera extract gel/spray. Comprehensive systemic therapy, including corticosteroids and immunosuppressants, was coordinated by a multidisciplinary team to control the autoimmune disease and its comorbidities. Conclusion: The presence of comorbidities, such as diabetes, further complicates systemic management and heightens the risk of secondary infections, requiring meticulous wound care. A multidisciplinary diagnostic algorithm, supported by supplementary examinations, is crucial for differentiating atypical BP from TEN and impetigo infection. Adequate management of associated oral and perioral manifestations is an integral component of comprehensive patient care.